SENSITIVITY AND SPECIFICITY OF ELISA TEST USING 30 KDA RECOMBINANT ANTIGEN TO DETECT Toxoplasma gondii INFECTION IN PIG WITH MICE BIOASSAY AS A GOLD STANDARD Nyoman Adi Suratma1????, I Made Bakta2, I Made Damriyasa3 - Adi Suratma, Nyoman; Bakta, I Made; Damriyasa, I Made (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Toxoplasmosis is a zoonotic disease caused by the protozoa Toxoplasma gondii.Primary infection in pregnant women can cause abortion, neonatal death or abnormalityof fetus. Accurate diagnosis is needed to prevent infection especially related to thepresence of cyst in the tissuesThe aim of this research was to study sensitivity and specificity of ELISAmethod with 30 kDa protein antigen to detect T.gondii infection in pig with micebioassay as gold standard.. Samples were 171 pigs slaughtered at pig slaughter house inDarmasaba BadungThe result showed that sensitivity of ELISA method was 100% and 90,7% inspecificity.Research about sensitivity using ELISA test to predict cysts presence in tissuewere needed in the future.
Keywords: Toxoplasma gondii , protein antigen 30 kDa, ELISA , bioassay.